Arsenic in wells at the Guayabo Caldera in Northwest Costa Rica - Martínez Cruz, María (2018)
The Guayabo Caldera, a 14 km diameter volcanic depression with Miravalles volcano rising 2028 ma.s.l. in the norte astern side of so called, formed by repeated eruption sand multiple collapses which dis membered earlier volcanoes between 1.5 to 0.6 m.y.ago. The pyroclastic-flow sheets represent more than 30 km 3 of dacitict or hyolitic magma associated to crystal fractionation processes.